INNOVATIVE TRANSFORMATIONS ACROSS COMPANIES OF HIGH-TECH INDUSTRIES - Ю. О. Єрешко; С. О. Кириченко (Ekonomìčnij Vìsnik Nacìonalʹnogo Tehnìčnogo Unìversitetu Ukraïni "Kiïvsʹkij Polìtehnìčnij Institut", 2024)
Modern conditions take a toll on global economies and society – war brings destruction and devastation, energy and economic crises, hunger, and decay. All of the above are being aggravated by the COVID-19 Pandemic. Be that as it may, they present both challenges and opportunities for companies to develop and innovate. War and crisis push economic agents even more toward innovation transformation. At the same time, the question remains: whether and when those innovations would be timely and effective. And what type exactly should be chosen? In order to answer those questions, the provided paper introduces a model for transforming innovation companies based on research into the motives driving the innovation process, its patterns and efficiency, and the actual reasons behind pursuing innovation. The model is built to be used in the future to ensure real innovative development of companies and, hence, the economy as a whole in a post-war recovery.